Frictionless segmented mechanics for controlled space closure - Ildeu Andrade Jr
ABSTRACT Extraction spaces may be needed to achieve specific orthodontic goals of positioning the dentition in harmony with the craniofacial complex. However, the fundamental reality that determines the occlusion final position is the control exerted by the orthodontist while closing the extraction spaces. A specific treatment objective may require the posterior teeth to remain in a constant position anteroposteriorly as well as vertically, while the anterior teeth occupy the entire extraction site. Another treatment objective may require the opposite, or any number of intentional alternatives of extraction site closure. The present case report describes a simple controlled segmented mechanic system that permitted definable and predictable force systems to be applied and allowed to predict the treatment outcome with confidence. This case was presented to the Brazilian Board of Orthodontics and Dentofacial Orthopedics (BBO) in partial fulfillment of the requirements for Diplomate certification.